2001
DOI: 10.1002/mar.1025
|View full text |Cite
|
Sign up to set email alerts
|

Deception in marketing research: Ethical, methodological, and disciplinary implications

Abstract: Although marketing researchers often find it necessary to deceive their research participants, little attention has been given within marketing to the ethical issues underlying the use of deception or to the potential consequences of deceptive research practices. This article provides a conceptual starting point for developing a more complete understanding of deception in marketing research, including an ethical analysis from the viewpoint of consequentialist and deontological theories of moral reasoning. A re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 54 publications
0
20
0
1
Order By: Relevance
“…Deceptive research practices also have potentially negative implications for the field, as they may reduce trust within the academic community and diminish public trust in research (Bok, 1978;Kimmel & Smith, 2001;Singer, 1984; but see Pittenger, 2002 for an alternative view).…”
Section: Methodological Implications Of Deceptionmentioning
confidence: 97%
See 1 more Smart Citation
“…Deceptive research practices also have potentially negative implications for the field, as they may reduce trust within the academic community and diminish public trust in research (Bok, 1978;Kimmel & Smith, 2001;Singer, 1984; but see Pittenger, 2002 for an alternative view).…”
Section: Methodological Implications Of Deceptionmentioning
confidence: 97%
“…Considerable attention has been given to deceptive marketing practices (Aditya, 2001;Darke & Ritchie, 2007;Tybout & Zaltman, 1974), but few studies present a formal ethical analysis. Studies that have applied normative theories of ethics to deception in research (Atwell, 1981;Baumrind, 1985;Kimmel & Smith, 2001;Pittenger, 2002;Reynolds, 1982;Toy, Wright, & Olson, 2001) generally do not develop sufficiently detailed analysis and prescriptions to offer specific guidance for experimental consumer research. This paper, in contrast, while building on these studies, applies from first principles social contract theory (SCT), a prominent theory of normative ethics increasingly found in business ethics (e.g., Bailey & Spicer, 2007;Dunfee, Smith, & Ross, 1999;Dunfee, 2006).…”
mentioning
confidence: 99%
“…As a consequence, the profession has succeeded in reducing the severity of deceptive methods used. Rosnow and Rosenthal, for instance, concluded that many of the seminal studies that were conducted then and that raised daunting ethical issues (e.g., Baumrind, 1964Baumrind, , 1971Baumrind, , 1985; see also Aguinis & Handelsman, 1997;Herrera, 1996;Kimmel & Smith, 2001) "would be impossible today" (p. 114).…”
Section: Ethical Implications Of Methodological Issuesmentioning
confidence: 99%
“…Such an approach generally would preclude the use of any deception in research, because to deceive would violate an overriding obligation to always be completely honest with participants (Kimmel & Smith, 2001). The utilitarian approach, which underlies the weighing of costs and benefits in determining whether deception may be acceptable, is problematic in application because of the practical difficulties in identifying the likelihood and degree of all the potential consequences of an investigation and in objectively weighing them in order to determine whether the study can be carried out as planned.…”
Section: Decision Making and The Morality Of Deceptionmentioning
confidence: 99%
“…Studies involving severe deceptions certainly are more difficult to justify when ethical principles are applied and are more likely to encounter problems when subjected to committee review, although mild deceptions also can be morally problematic. In fact, from some moral philosophy perspectives (e.g., certain duty-based theories), deception can be morally wrong even where the consequences are insignificant (Kimmel & Smith, 2001).…”
Section: Types and Severity Of Research Deceptionsmentioning
confidence: 99%